(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Low birth weight (LBW) is one of the pernicious outcomes of pregnancy. To recognize the factors contributing to LBW is therefore of vital significance. But due attention had not been paid to address the issue. This study was carried out to candle the light on maternal demographic and health services factors on birth weight of a newborn baby. Objective: To depict the pattern of birth weight of newborn babies born at CMH Dhaka and to ascertain selected demographic (age, height) pattern and utilization of health service factors of the mothers. Materials and Methods: This cross-sectional study was conducted at Combined Military Hospital (CMH) Dhaka from September to December 2011 among 110 respondents. Data were collected by interview using a semi-structured questionnaire and were checked, edited, coded, categorized, cleaned and analyzed by using SPSS version 16. Results: Mothers’ age ranged from 19 to 36 years. Highest 43.6% of mothers belonged to the 20-25 years age group. Teenage mothers were 15.5%. Mothers above 25 years of age gave birth to higher percentage of average weight babies (88.9%) and teenaged (<20 years) mothers gave birth to a higher percentage of LBW babies (17.7%). About 44.5% mothers belonged to height 150-155 cm. Short stature mothers with height 150 cm and below were 16.4% and produced more (33.3%) LBW babies. As the height of the mothers increases, the babies born with better birth weight. The result was statistically significant (p<0.05). All the mothers had antenatal check-up. Highest number of mothers had 4-6 visits. Rate of LBW babies were found highest (31.8%) among the mothers who had minimum number of visits (1-3 visits). Mothers with 7-9 visits had lowest number of LBW babies (4.3%). Proportion of higher birth weight babies (>3500 gm) increased as the number of visits increased. The result was statistically significant (p < .05). Conclusion: All these findings suggests that a substantial evidence of demographic factors like age of the mother during pregnancy and height of the mother and utilizing the health care facilities for antenatal care has an effect on birth weight. Ensuring health care facilities and addressing demographic factors like age of women during marriage, condition can be improved. JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 26-29